2021
DOI: 10.1002/jcp.30020
|View full text |Cite
|
Sign up to set email alerts
|

Repair of articular cartilage defect using adipose‐derived stem cell‐loaded scaffold derived from native cartilage extracellular matrix

Abstract: The purpose of this study was to investigate the feasibility of adipose-derived stem cells (ADSCs) as the seed cells of cartilage tissue engineering. ADSCs were isolated from adipose tissue that was harvested under sterile conditions from the inguen fold of porcines and cultured in vitro. Acellular cartilage extracellular matrix (ACECM) scaffolds of pigs were then constructed. Moreover, inflammatory cells, as well as cellular and humoral immune responses, were detected using hematoxylin and eosin staining stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The composite scaffold improved cell proliferation and enhanced the chondrogenic-like differentiation of ADSCs. In addition, studies have revealed the beneficial effects of an injectable hydrogel consisting of glycol chitosan/dibenzaldehyde-terminated polyethylene glycol [ 119 ] or acellular cartilage ECM scaffolds [ 120 ] combined with ADSCs on cartilage tissue repair and regeneration.…”
Section: Adscs and Adsc-based Therapies For Musculoskeletal Regenerationmentioning
confidence: 99%
“…The composite scaffold improved cell proliferation and enhanced the chondrogenic-like differentiation of ADSCs. In addition, studies have revealed the beneficial effects of an injectable hydrogel consisting of glycol chitosan/dibenzaldehyde-terminated polyethylene glycol [ 119 ] or acellular cartilage ECM scaffolds [ 120 ] combined with ADSCs on cartilage tissue repair and regeneration.…”
Section: Adscs and Adsc-based Therapies For Musculoskeletal Regenerationmentioning
confidence: 99%
“…Likewise, another study by Lu et al proved the effectiveness of ADSC-ACECM composites for repairing cartilage defects, showing the promising prospects of this tissueengineered biomaterial (Figure 9B). [176] A clinical trial conducted by Lee et al evaluated the efficacy and safety of intra-articular ADSC injections for the treatment of osteoarthritis. Autologous ADSCs were administered intraarticularly to 12 patients with knee osteoarthritis.…”
Section: Adscs For Cartilage Regenerationmentioning
confidence: 99%
“…Reproduced with permission. [176] Copyright 2020, John Wiley and Sons. improvement and pain relief were observed in all treatment groups, whereas statistical significance was identified only in patients treated with a low dose.…”
Section: Adscs For Cartilage Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies support that autologous, allogenic, and xenogenic human MSC administration bolsters osteochondral reconstitution in pigs. Porcine aMSCs seeded onto decellularized cartilage extracellular matrix (DCECM) performed similarly to chondrocytes regarding histological chondral defect regeneration ( Lu L. et al, 2021 ). Scaffold-free implantation of porcine bMSCs and aMSCs at 5–30 million cells per defect, respectively, also improved cartilage histological and MRI score compared to nontreatment ( Yamasaki et al, 2019 ; Theruvath et al, 2021 ).…”
Section: Large Animal Models For Msc-based Articular Cartilage Regene...mentioning
confidence: 99%